2011
DOI: 10.1093/cvr/cvr239
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of aldolase B and overproduction of methylglyoxal in vascular tissues from rats with metabolic syndrome

Abstract: Upregulation of aldolase B by accumulated fructose is a common mechanism for MG overproduction in VSMCs and aorta in different models of metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 39 publications
1
75
0
Order By: Relevance
“…It was reported that the expressions of GLUT5 (fructose transporter) and an MGO synthase, aldolase B, increased in SHR aorta, while the expression of other MGO synthases including SSAO or CYP 2E1 and plasma glucose level did not increase (23,24). It was thus proposed that increased MGO accumulation was mediated via aldolase B through increased fructose transporting in vascular tissues of SHR.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that the expressions of GLUT5 (fructose transporter) and an MGO synthase, aldolase B, increased in SHR aorta, while the expression of other MGO synthases including SSAO or CYP 2E1 and plasma glucose level did not increase (23,24). It was thus proposed that increased MGO accumulation was mediated via aldolase B through increased fructose transporting in vascular tissues of SHR.…”
Section: Discussionmentioning
confidence: 98%
“…It has recently been argued that all therapeutic strategies for the prevention of complications associated with diabetes rely on the premise that the deleterious effects of high glucose levels and an enhanced metabolic flux are mediated by the generation of toxic metabolites (3,4). Of these, reactive a-dicarbonyls like MG are among the most important (6).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the setting of diabetes, excessive glycolytic flux with reduced activity of GAPDH (5) and an overactive polyol pathway (4) leads to the accumulation of triose phosphate intermediates and their spontaneous fragmentation into MG (5). The proatherogenic effects of fructose feeding and the metabolic syndrome may also be partly ascribed to increased generation of MG through the polyol pathway (4). MG production may also rise in the absence of hyperglycemia via oxidation of aminoacetone (generated during protein catabolism) by semicarbazide-sensitive amine oxidase, the oxidation of ketone bodies by myeloperoxidase, and/or the cytochrome P450-mediated oxidation of acetone (generated from lipolysis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive levels of the glycolysis metabolite methylglyoxal (MG) in vivo, that contribute to increased carbonyl stress, are associated with conditions such as diabetes, renal failure, obesity and metabolic syndrome [4][5][6][7][8][9]. In diabetes, increased levels of MG are implicated in the pathogenesis of vascular complications such as hypertension [10], impaired microcirculation [11], and thrombosis [12].…”
Section: Introductionmentioning
confidence: 99%